INTEGRATING ISLAMIC HUMANITARIANISM AND MODERN ULAMA PERSPECTIVES: CHILD PROTECTION IN INDONESIA'S POLICY FRAMEWORK - Hidayat, Riyan Erwin; Faizin, Mu'adil; Hakim, Abdul; Karimullah , Suud Sarim; Rohmah, Umdah Aulia (UIN Antasari Banjarmasin, 2024)
This study examines the integration of Islamic humanitarian values and modern ulama thoughts in shaping child protection policies in Indonesia. Grounded in Islamic values, including insights from Qur’anic injunctions and prophetic traditions, it highlights the parental responsibilities of safeguarding children's education, health, and overall well-being. Fathers are assigned the duty of providing sustenance, while mothers are entrusted with the primary role of nurturing and caring for their children, as emphasized by scholars such as Wahbah az-Zuhaili and Sayyid Sabiq. The findings illustrate how these principles align with Indonesia's cultural and social contexts, offering a comprehensive framework for addressing child labor and exploitation. The study presents actionable recommendations, including strengthening legal frameworks rooted in Islamic humanitarian values, empowering families through education on children’s rights, and fostering collaboration among policymakers, religious leaders, and civil society. By integrating Islamic values with contemporary challenges, this article contributes novel perspectives to the discourse on child protection, proposing culturally relevant and ethically grounded solutions. These insights aim to guide the development of effective, child-centered policies that uphold both humanitarian and Islamic ideals